Bitter Orange (Citrus aurantium L.) Intake Before Submaximal Aerobic Exercise Is Safe for Cardiovascular and Autonomic Systems in Healthy Males: A Randomized Trial - Benjamim, Cicero Jonas R.; Júnior, Francisco Welington de Sousa; Porto, Andrey Alves [UNESP]; Rocha, Élida Mara B.; Santana, Milana D.; Garner, David M. [UNESP]; Valenti, Vitor E. [UNESP]; Bueno Júnior, Carlos Roberto (Frontiers, 2022)
Background: There are still no studies of the cardiovascular safety of the isolated use of Citrus aurantium in aerobic submaximal exercise. Objective: To evaluate the effect of C. aurantium supplementation on the recovery of cardiorespiratory and autonomic parameters following a session of submaximal aerobic exercise. Methods: Twelve healthy male adults achieved a crossover, randomized, double-blind, and placebo-controlled trial. C. aurantium (600 mg, p-synephrine at 30% amount [180 mg]) or placebo (600 mg of starch) were ingested 90 min before evaluation in randomized days. We evaluated systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP), mean arterial pressure (MAP), heart rate (HR) and, HR variability indexes at Rest and during 60 min of recovery from exercise. Results: Citrus aurantium ingestion accelerated the reduction in SBP after exercise, anticipated the return of vagal modulation of the heart after exercise via the HF (ms2), pNN50 (%), and 2 UV% indices. Moreover, rushed the output of sympathetic modulation after exercise via the 0V% index. No unfavorable cardiovascular effects were achieved for HR, DBP, PP, and MAP parameters. Conclusions: Citrus aurantium was shown to be safe for the cardiovascular and autonomic systems alongside submaximal aerobic exercise in healthy males.
Keywords: autonomic nervous system; blood pressure; heart rate control and regulation; p-synephrine; parasympathetic nervous system; physical effort